Acot1 is a sensitive indicator for PPARα activation after perfluorooctanoic acid exposure in primary hepatocytes of Sprague-Dawley rats. (August 2017) - Liu, Hui; Wang, Jianshe; Sheng, Nan; Cui, Ruina; Pan, Yitao; Dai, Jiayin
Abstract: Perfluorooctanoic acid (PFOA) is one of the most commonly detected and persistent perfluoroalkyl substances (PFASs) found in the environment. We found that cell viability and intracellular oxidant stress increased in primary rat hepatocytes exposed to PFOA (100 μM PFOA, 24 h), and mitochondrial superoxide increased from 6.25 μM PFOA treatment group. To screen for sensitive indicators in mRNA level, we investigated global transcriptome profile alteration after PFOA exposure using RNA-sequencing (RNA-seq) in primary rat hepatocytes, and identified 177 gene transcripts (158 upregulated, 19 downregulated) as significantly changed after exposure to 100 μM of PFOA for 24 h (fold change ≥ 2, FDR < 0.05). Quantitative PCR (qPCR) and RNA-fluorescence in situ hybridization (RNA-FISH) assays were conducted after PFOA treatment at various doses (0, 0.4, 1.56, 6.25, 25, and 100 μM) and times (6, 12, 18, 24, 48, and 96 h). Acot1 transcripts increased significantly in the 100 μM PFOA group (4500-fold) after 24 h of exposure, and increased remarkably for all time points (24, 48, 72 and 96 h) after exposure to 6.25 μM. Acot1 also responded to lower PFOA doses, with a significant increase found after exposure to 0.4 μM for 96 h. These results imply Acot1 could serve as a sensitive indicator for PPARα activation after PFOA exposure in primary rat hepatocytes. Highlights: Cell viability and intracellular oxidant stress were not sensitive for PFOA exposure. Transcriptome profile identified 177 changed transcripts after PFOA exposure. Acot1 was the most sensitive DEG transcript. Acot1 is a sensitive indicator for PPARα activation after PFOA exposure.